2016
DOI: 10.1210/en.2016-1218
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Exacerbate Nociceptive Pain via Up-Regulation of TRPV1 and ANO1 in Trigeminal Primary Neurons of Female Rats

Abstract: Several trigeminal pain disorders show sex differences, and high levels of estrogens may underlie these differences. The interaction between transient receptor potential vanilloid 1 (TRPV1) and anoctamin 1 (ANO1) plays an important role in peripheral nociception. However, whether TRPV1 and ANO1 are involved in estrogen-modulated trigeminal pain sensitivity is unclear. In this study, we examined estradiol (E2) modulation of nociception through behavioral and immunohistological experiments after application of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 43 publications
1
30
0
2
Order By: Relevance
“…By influencing the transcription of certain genes ( mitogen-activated protein kinase-1 , interleukin-1 receptor type I , bradykinin B2 receptor , GABA transporter protein , GABA A receptor subunit a6, opioid receptor-like 1 receptor , purinoreceptor P2X3 , transient receptor potential vanilloid 1 and neuropeptide Y ) with potential relevance to craniofacial pain, long-lasting changes were reported in different cells. 35 , 40 , 43 46 Estrogen can activate intracellular signaling pathways via non-genomic, membrane-mediated mechanisms also, which may occur within seconds or minutes. 40 , 47 50 These cellular mechanisms affect numerous processes, which are essential in trigeminal pain perception including the function of endogenous anti-nociceptive system, 51 , 52 the modulation of the excitability of TNC neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By influencing the transcription of certain genes ( mitogen-activated protein kinase-1 , interleukin-1 receptor type I , bradykinin B2 receptor , GABA transporter protein , GABA A receptor subunit a6, opioid receptor-like 1 receptor , purinoreceptor P2X3 , transient receptor potential vanilloid 1 and neuropeptide Y ) with potential relevance to craniofacial pain, long-lasting changes were reported in different cells. 35 , 40 , 43 46 Estrogen can activate intracellular signaling pathways via non-genomic, membrane-mediated mechanisms also, which may occur within seconds or minutes. 40 , 47 50 These cellular mechanisms affect numerous processes, which are essential in trigeminal pain perception including the function of endogenous anti-nociceptive system, 51 , 52 the modulation of the excitability of TNC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the effect may be in part due to the estrogen-dependent increases in mRNA of transient receptor potential vanilloid 1 and anoctamin 1 in TNC, which have important role in trigeminal pain. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the major non-psychoactive component of cannabis, cannabidiol (CBD), is emerging as a cannabis constituent with potentially diverse therapeutic effects, but there are almost no sex comparisons of its effects, even in animals. Given the emerging evidence that TRPV1 channels-a major CBD target-are estradiol-modulated (Yamagata et al, 2016), examining sex differences in a variety of CBD effects is warranted.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…When estrogen levels were monitored, either as a function of the estral cycle or its replacement after ovariectomy in rodents, it was observed that under low levels of 17β-estradiol, capsaicin produced a mild nocifensive response (Lu et al, 2009 ; Yamagata et al, 2016 ). In marked contrast, high levels of 17β-estradiol (proestrus) resulted in a lower mechano- and thermo-nociceptive threshold, thereby promoting mechanical and thermal sensitization (Payrits et al, 2017 ).…”
Section: Trpv1 and Estrogensmentioning
confidence: 99%
“…The molecular mechanisms involved in 17β-estradiol-induced sensitization of TRPV1 appeared to include both a genomic regulation of channel expression and a functional modulation. Regarding the long-term effect of estrogens in females, several studies showed a transcriptional-induced expression of TRPV1 by 17β-estradiol in nociceptors (Yamagata et al, 2016 ; Kumar et al, 2017 ; Payrits et al, 2017 ). Even sensory neurons derived from female mouse stem cells showed that the application of 17β-estradiol increased the expression of TRPV1 mRNA (Greaves et al, 2014 ).…”
Section: Trpv1 and Estrogensmentioning
confidence: 99%